Functional analysis of lower limbs in individuals infected with the human immunodeficiency virus - Silva, Gabriel Pádua; Ferreira, Bruno; Siéssere, Selma; Regalo, Isabela Hallak; Esposto, Danilo Stefani; Gonçalves, Camila Roza; Arnoni, Veridiana Wanshi; Verri, Edson Donizetti; Vasconcelos, Paulo Batista; Vasconcelos, Maria Aparecida Carneiro; Machado, Alcyone Artioli; Regalo, Simone Cecilio Hallak (International Journal of Health Sciences, 2018)
Objectives: The objective of this research was to analyze the functional changes of lower limbs by means of surface electromyography in patients with acquired immunodeficiency syndrome. Methods: Sixty men and women (age mean of 36.77± 9.33 years) were divided into two groups: 30 individuals with HIV subtype 1 (HIVG), and 30 healthy individuals (CG). Muscle activity was evaluated using surface electromyography (sEMG). sEMG measurements were made while the subjects assumed the static positions: rest in orthostatism (RS), squat (SQ) "normalization factor", right and left single leg support (RSLS, LSLS) and during functional activities: right and left single leg step rise (RSLSR, LSLSR) and step down (RSLSD, LSLSD), rising and seating on a chair (RC, SC). Results: To sEMG results revealed statistically significant values in the conditions of RSLS to left semitendinosus muscle, for LSLS to right and left semitendinosus, right rectus femoris and right gluteus medius muscles, for LSLSR to right rectus femoris and right tensor fasciae latae muscles, for RSLSD to right and left semitendinosus and right rectus femoris muscles, for RC to right rectus femoris and left gluteus medius muscles and for SC to right semitendinosus, right rectus femoris and right and left gluteus medius muscles. Conclusion: It can be concluded that individuals with acquired immunodeficiency syndrome presented changes in lower limb muscle activity.